Penetration Impact of Distributed Generation of Wind Turbines on PLN’s Electric Distribution Network at Krueng Raya Aceh Besar - Renno Kamal Putra; Muhammad Daud; Adi Setiawan; Arnawan Hasibuan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Distribution of electricity that is too far away can cause the power flow that flows in the distribution channel to be significantly reduced. This also occurs in the PLN distribution line in Krueng Raya Aceh Besar, which is 95 km away, so that the voltage value is often below the standard value. This study analyzes the use of dispersed generators as an alternative solution to overcome this problem while increasing the efficiency of the electricity distribution system. However, the operation of distributed generators can have an impact on distortion harmonics in the voltage, current, and frequency of the power flow in the distribution network system. This study is focused on analyzing the penetration impact of dispersed wind energy generators on the distribution line by conducting simulations using ETAP. The results can increase the average value of the voltage profile by 0.077 kV or 0.39%, reduce power losses by 6.628 kW and THDv values ​​by 0.004% to 0.018% and THDi by 0 on all buses. Penyaluran listrik yang terlalu jauh dapat menyebabkan aliran daya yang mengalir dalam saluran distribusi berkurang secara signifikan. Ini juga terjadi pada saluran distribusi PLN di Krueng Raya Aceh Besar yang jaraknya mencapai 95 km sehingga nilai tegangannya sering berada di bawah nilai standar. Penelitian ini menganalisis penggunaan pembangkit tersebar sebagai alternatif solusi untuk mengatasi masalah tersebut sekaligus meningkatkan efisiensi sistem distribusi listrik. Namun, pengoperasian pembangkit tersebar dapat menimbulkan distorsi harmonisa pada tegangan, arus, dan frekuensi pada aliran daya dalam sistem jaringan distribusi. Studi ini difokuskan pada analisis dampak penetrasi pembangkit tersebar energi angin pada saluran distribusi dengan melakukan simulasi menggunakan ETAP. Hasil penelitian dapat meningkatkan nilai rata-rata profil tegangan sebesar 0,077 kV atau 0,39%, mengurangi rugi-rugi daya sebesar 6,628 kW serta nilai THDv sebesar 0,004% sampai 0,018% dan THDi sebesar 0 pada seluruh bus.